To Leave or Stay: Plans of Bulgarian Citizens in the UK after Brexit - Markova, Eugenia; Tosheva, Ekaterina (Research Papers, 2021)
Britain's exit from the European Union affects the plans of Bulgarian immigrants there. They are a significant number that has been growing steadily over the last 15 years and even contrary to expectations since the European referendum in June 20016. Based on an online survey of 361 Bulgarians living in the country, conducted in the period March-April 2019, this article reveals the attitudes and expectations of the respondents about changes in their lives as a result of BREXIT. Bulgarians of different ages, with different socio-demographic characteristics and different status on the labor market are covered. Special emphasis is placed on the plans of the Bulgarians to change their place of residence – return to Bulgaria or move to another country. The analysis reveals that factors such as age, education, length of stay in the UK and the degree of integration into the labor market influence the decision of our compatriots to leave or stay in the UK.
Keywords: Empirical research; BREXIT; Bulgarian immigrants; Labour market integration; Returning migrants; UK